2003
DOI: 10.1034/j.1600-0765.2003.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic relatedness of Porphyromonas gingivalis clinical and laboratory strains assessed by analysis of insertion sequence (IS) element distribution

Abstract: Transposition and recombination between IS elements are not sufficiently pervasive to obscure strain relationships, though this does not preclude the possibility that such events play an important role in allowing P. gingivalis to adapt to new environments. Given the level of genetic diversity observed, it may be especially important to examine genetically diverse strains when drawing conclusions based on the W83 P. gingivalis genomic database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…From mapping the distribution of IS elements in several P. gingivalis laboratory strains and clinical isolates, Califano et al (7) suggested a preserved strain relationship reflecting the fact that neither recent transposition nor homologous recombination between IS copies had occurred extensively in the isolates studied. However, Califano et al (7) emphasized that their results do not imply that genomic variation caused by IS elements never occurred or that the transposition between IS elements is not im-portant in adapting to new environments. Evidence of genomic rearrangement has been detected where a gene is interrupted with an IS sequence (45).…”
Section: Discussionmentioning
confidence: 99%
“…From mapping the distribution of IS elements in several P. gingivalis laboratory strains and clinical isolates, Califano et al (7) suggested a preserved strain relationship reflecting the fact that neither recent transposition nor homologous recombination between IS copies had occurred extensively in the isolates studied. However, Califano et al (7) emphasized that their results do not imply that genomic variation caused by IS elements never occurred or that the transposition between IS elements is not im-portant in adapting to new environments. Evidence of genomic rearrangement has been detected where a gene is interrupted with an IS sequence (45).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we selected 10 transconjugants from a W83Em-33277Tc mating and analyzed these strains by Southern hybridization to determine the extent of genome chimerization. Chromosomal DNA digests were probed with ISPG4, an insertion sequence that has nine copies in W83 and none in 33277 (6). As shown in Fig.…”
Section: Presence Of Type Iv-related Elements In P Gingivalis Strainsmentioning
confidence: 99%
“…Numerous studies have attempted to measure the degree of genetic variability in the P. gingivalis population by using techniques such as pulsed-field gel electrophoresis, restriction fragment length polymorphisms, insertion sequence hybridization, cross-species microarray hybridization, and multilocus sequence typing (2,6,7,10,15,24,27). All studies to date have pointed to significant levels of genetic variation among P. gingivalis strains, indicating that the population structure of these organisms is not strictly clonal but instead is influenced by DNA recombination between different strains.…”
mentioning
confidence: 99%
“…In multispecies communities such as the dental biofilm, the possibilities for genetic exchange probably increase even more, as there is a constant supply of genetic material released from scores of Gram-positive and Gram-negative species of bacteria. Not surprisingly, many of the sequenced oral bacteria show a plethora of insertion sequences and other evidence of transposition (Califano et al, 2003;Kapatral et al, 2002). This is also true for S. mutans, which contains a variety of loci that appear to have resulted from horizontal gene transfer (Ajdić et al, 2002).…”
Section: Introductionmentioning
confidence: 99%